(untitled) (Bulletin KNOB, 2014)
The article discusses the design and the construction of the first poured-concrete house in the Netherlands. Where did the idea originate, who developed it and who played a part in realizing the house? Both aesthetic and technical aspects are discussed. While the civil engineers H.J. Harms and George Small were responsible for the construction, the artist Herman Hana greatly influenced the exterior of the building. Hana probably showed the design to H.P. Berlage, who was himself very interested in this new construction technique and had written an article about pouring houses. Berlage saw concrete as the building material of the future. Together with Harms, his cousin, Hana was the driving force behind the building of the house. The article also pays attention to how the idea and the construction itself were received and reviewed in the local and national press and to the end result of the enterprise. Opinions tended to differ. Although the construction was presented by the initiators with much enthusiasm – they considered the result a success and proclaimed it to be the beginning of a machinist era – it didn’t gain much following. In the Netherlands, the experiment in Santpoort remained the only one of its kind and those involved suffered considerable financial losses. Still, in many other parts of the world many poured-concrete houses would be built by others. Harms and Small did build another house with the technique that was developed by Thomas Edison and with their patented cast mixture, in Saint-Denis (Paris), but Hana was no longer involved. It turned out to be the last convulsion of an enterprise that had nevertheless given quite an impulse to thinking about the use of concrete in the building industry. The building in Santpoort had a very different look from the cast-concrete house that Edison had envisioned and for which he had applied a patent in 1908. The mix was made according to the specifications as defined in the patent by the initiators, Small and Harms. The aesthetics corresponded to the innovative nature of the construction method. There was no ornamentation and the building had a flat roof. The visual effect of the building was regarded as ‘odd’. The building industry did not see the house as a prototype for large-scale production in answer to the increasing shortage in housing. It wasn’t until after the First World War ended in 1918 that the house in Santpoort was looked at again, but continuing on the path of pouring was not considered a viable option. Meanwhile, other techniques for building in concrete had been developed and were busily experimented with.